Risky Decision Making Assessed With the Gambling Task in Adults with HIV - Hardy, David J. (2006)
Decision making was assessed using a laboratory gambling task in 67 adults with the Human Immunodeficiency Virus (HIV+) and in 19 HIV-seronegative (HIV−) control participants. Neurocognitive test performance across several domains was also analyzed to examine potential cognitive mechanisms of gambling task performance. As predicted, the HIV+ group performed worse on the gambling task, indicating greater risky decision making. Specifically, the HIV+ group selected more cards from the “risky” or disadvantageous deck that included relatively large payoffs but infrequent large penalties. The control group also selected such risky cards but quickly learned to avoid them. Exploratory analyses also indicated that in the HIV+ group, but not in the control group, gambling task performance was correlated with Stroop Interference performance and long delay free recall on the California Verbal Learning Test, suggesting the role of inhibitory processes and verbal memory in the poorer gambling task performance in HIV. These findings indicate the usefulness of the gambling task as a laboratory tool to examine risky decision making and cognition in the HIV population.